Mackinder and the Arctic's Emerging Geopolitics: Recommendations for the U.S. and Its NATO Allies - Chapman, Bert (Purdue University, 2018)
This presentation shows how Halford Mackinder (1861-1947) described Canada and the Arctic region in his geopolitical writings. It goes on to stress how the Arctic is becoming increasingly important in international geopolitical policymaking due to its significant oil and natural gas resources, how warming temperatures are increasing international access to its waters, and the how countries as diverse as Canada, China, Russia, and the U.S. see the Arctic region in their strategic policymaking. It concludes by stressing that the Arctic can no longer be viewed as a region immune from international conflict and presents recommendations for the U.S. and its NATO allies to keep powers such as China and Russia from threatening international freedom of navigation and movement from injuring the strategic interests of the U.S. and its allies.